HUBUNGAN KEPATUHAN PENGGUNAAN OBAT DENGAN KUALITAS HIDUP PASIEN PENDERITA HIPERTENSI DI KECAMATAN LAGUBOTI KABUPATEN TOBA - Andi josep Nicolas Hutahaean; Meliani Dwi Lestari; Harsan Arifin Kasan; Janly Pangaribuan (Jurnal Ilmu Kesehatan Abdurrab, 2024)
Hypertension is a "silent killer" which is generally known by the public as high blood pressure. Hypertensive patients who do not undergo long-term medication therapy will cause complications and discomfort so that it will affect the quality of life. This condition can be prevented and overcome by routine drug therapy. The purpose of this study was to determine the relationship between drug compliance and the quality of life of hypertensive patients in Laguboti District, Toba Regency. This research method is a cross-sectional survey, a correlation study to find a relationship between risk factors (independent) and their effects or influences (dependent). The sample in this study consisted of 42 hypertensive patients in Simatibung Village and Op. Raja Hutapea Timur Village. Data collection used a simple cluster random sampling technique. The data analysis technique used was the Spearman test. This study states that drug compliance in hypertensive patients states that 52.4% have moderate compliance with a quality of life level of 59.5% have a high quality of life. Based on the results of the Spearman test, the results. Sig. Value. (2-tailed) is 0.736 > 0.05, it can be concluded that there is no significant correlation between drug compliance and quality of life. This study is expected to improve drug compliance and quality of life.